2015
DOI: 10.1371/journal.pone.0142195
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute and Chronic Social Stress on the Hippocampal Transcriptome in Mice

Abstract: Psychogenic stress contributes to the formation of brain pathology. Using gene expression microarrays, we analyzed the hippocampal transcriptome of mice subjected to acute and chronic social stress of different duration. The longest period of social stress altered the expression of the highest number of genes and most of the stress-induced changes in transcription were reversible after 5 days of rest. Chronic stress affected genes involved in the functioning of the vascular system (Alas2, Hbb-b1, Hba-a2, Hba-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 126 publications
(160 reference statements)
9
95
0
Order By: Relevance
“…This is congruent with a previous study showing that 8 days of stress increased CTGF (36). Because CTGF is also known to interact with numerous molecules, and the signaling and feedback is extremely complex, more research on CTGF is needed to elucidate the dynamics of the stress response.…”
Section: Discussionsupporting
confidence: 93%
“…This is congruent with a previous study showing that 8 days of stress increased CTGF (36). Because CTGF is also known to interact with numerous molecules, and the signaling and feedback is extremely complex, more research on CTGF is needed to elucidate the dynamics of the stress response.…”
Section: Discussionsupporting
confidence: 93%
“…(9) reported acute stress-induced reduction in expression of a set of genes in hippocampal samples that overlap with those reported here (Fig. 1) and in the Cho et al .…”
supporting
confidence: 89%
“…As DAMPs, Mrp8 and its binding partner Mrp14 are upregulated after chronic stress exposure [26] and impact numerous inflammatory diseases [42]. Our findings showed that Mrp8 and Mrp14 increased with depressive-like behaviors in CUMS-treated mice.…”
Section: Discussionmentioning
confidence: 55%